The Impact of Islamic Law Principles in The Use of Documentary Evidence - Dr. Ashigar Abubakar; Dr. Ibrahim Aliyu Shehu (Journal of Current Research and Studies, 2025)
The paper delved into the importance of writing and the promotion of all transaction among the Ummah to be documented in a safe and secured manner. This notion is in line with the areas of documentary evidence by considering the authorities associated with documentary findings as most cases are dependent upon the circumstance, through which such document is secured and produced for evidential value. The paper also tries to look at what a document is confined to be, its content and what information it provides for the sake of admissibility associated with the required testimony before a court of law or any judicial tribunal or panel of inquiry. The paper further considered the modern reforms provided in the areas of documentary evidence in our modern world, i.e evidential value of the modern electronic and other forms of evidence in forms of document or from other perspective associated with it. The paper concluded by providing some useful findings, recommendations towards the present global sophistication in the area of documentary evidence. These sophistications that can be made available to our court to utilizes for the sake of providing the needed justice delivery to all parties before our courts. As evidence is an information that tends to establish a fact which is materially important to an investigation and which may assist in substantiating or disproving an allegation, whether physical or documentary.